Patients' Perception of Waiting Time and Pharmacy Service of Hospital X Bali - Antari, Ni Putu Udayana; Megawati, Fitria; Suwantara, I Putu Tangkas; Palguna, I Gede Rizky; Widnyani, Ni Kadek Indah Amelia; Wahyuni, Ni Wayan Mita Sri (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2026)
Background: Many hospitals are having problems with waiting times. Meanwhile, the effect of waiting time on perceived pharmacy service quality is inconsistent. Waiting time and pharmacy service quality can influence a hospital's image through patient perception.Objectives: To identify factors influencing patients' perceptions of waiting time and pharmacy service quality.Methods: The study used a cross-sectional design with one hundred samples, which were taken using the convenience sampling method. Data were collected using questionnaires and direct observation at Hospital X and analyzed using SPSS version 26 in a 95% CI.Results: Actual and patient-perceived waiting times differed significantly (Wilcoxon test, P-value 0.005). Age significantly affected patient perceptions of pharmacy service quality in both bivariate and multivariate tests (Chi-square: P-value 0.032; Logistic regression: P-value 0.023, adjusted OR: 2.594 (Min: 1.138; Max: 5.912)). Even though included in the equation, the actual waiting time is not significantly associated with patient perceptions.Conclusion: Patients did not perceive waiting times in accordance with the actual waiting time because emotional factors easily influence the perception of time. Pre-elderly and elderly patients at Hospital X perceive pharmacy services dominantly as good quality. Age significantly influences patients' perception of pharmacy service quality. Actual waiting time may influence patients' perception of pharmacy service quality if other factors are controlled. Hospitals should consider age and emotional factors when waiting for services to maintain patients' good perceptions of pharmacy service.